23=-6x-67

Simple and best practice solution for 23=-6x-67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23=-6x-67 equation:


Simplifying
23 = -6x + -67

Reorder the terms:
23 = -67 + -6x

Solving
23 = -67 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
23 + 6x = -67 + -6x + 6x

Combine like terms: -6x + 6x = 0
23 + 6x = -67 + 0
23 + 6x = -67

Add '-23' to each side of the equation.
23 + -23 + 6x = -67 + -23

Combine like terms: 23 + -23 = 0
0 + 6x = -67 + -23
6x = -67 + -23

Combine like terms: -67 + -23 = -90
6x = -90

Divide each side by '6'.
x = -15

Simplifying
x = -15

See similar equations:

| 26/-6 | | 12m+37+13n+4m-9n= | | -68-(-30)= | | X/22+2=-1 | | 7x^2-89x-126=0 | | 2p-9=5p/12 | | 70+2x-2=90 | | (x^-9y)^-8/(x^9y^-1)^8 | | 12y=36+6y | | 2(7x+5)-1=14x+9 | | 2m+18=60 | | 95*(-16)= | | 6(3n-1)=8n+24 | | 5i(4+3i)= | | -8x+79=-25 | | 1v+1=-20 | | 4+2(1+x)=8 | | 16-3*-2=x | | 28+(+63)= | | 12x-5x-10y+y= | | .20(45-x)=x^2 | | -7x+8=13 | | x-4.5=2.5 | | -5(-2-3z)-8v=25 | | 23+(+20)= | | 12k+14=10k-2k-14 | | 5/6x-3+1/3x=7/24x+1/8 | | s=25+0.75 | | -9=-4+x/17 | | n+(-4)+(-6n)+(-10)= | | 3a+11=-4 | | -4p-2p+8p-15+3= |

Equations solver categories